2018
DOI: 10.1038/s41598-018-30087-4
|View full text |Cite|
|
Sign up to set email alerts
|

Antenatal IL-1-dependent inflammation persists postnatally and causes retinal and sub-retinal vasculopathy in progeny

Abstract: Antenatal inflammation as seen with chorioamnionitis is harmful to foetal/neonatal organ development including to eyes. Although the major pro-inflammatory cytokine IL-1β participates in retinopathy induced by hyperoxia (a predisposing factor to retinopathy of prematurity), the specific role of antenatal IL-1β associated with preterm birth (PTB) in retinal vasculopathy (independent of hyperoxia) is unknown. Using a murine model of PTB induced with IL-1β injection in utero, we studied consequent retinal and cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 73 publications
(115 reference statements)
2
25
0
Order By: Relevance
“…Current ROP treatments employ anti-vascular endothelial growth factor (VEGF) antibodies and laser photocoagulation (Hellström et al, 2013) which treat the proliferative phase of the disease but fail to address earlier stage vaso-obliteration and associated inflammation. Modulation of IL-1R signaling offers the potential to mitigate both PTB and ROP as indicated by the in vivo results herein and previously reported (Rivera et al, 2013; Nadeau-Vallée et al, 2015, 2017; Beaudry-Richard et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Current ROP treatments employ anti-vascular endothelial growth factor (VEGF) antibodies and laser photocoagulation (Hellström et al, 2013) which treat the proliferative phase of the disease but fail to address earlier stage vaso-obliteration and associated inflammation. Modulation of IL-1R signaling offers the potential to mitigate both PTB and ROP as indicated by the in vivo results herein and previously reported (Rivera et al, 2013; Nadeau-Vallée et al, 2015, 2017; Beaudry-Richard et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Recent evidences showed that choroidal thinning is present in adolescents and adults formerly affected with ROP (Wu et al, 2013;Erol et al, 2016;Rivera et al, 2017b). Similarly, our group also detected a sustained choroidal thinning in different animal models of ROP (Shao et al, 2011;Zhou et al, 2016;Beaudry-Richard et al, 2018). To date, several studies have focused their effort in developing novel anti-angiogenic monotherapy against the aberrant NV, by using anti-growth factors such as anti-VEGF, -FGF, -IGF and their receptors (Cabral et al, 2017).…”
Section: Introductionsupporting
confidence: 73%
“…As a result, early inflammation should be regarded as a main risk factor for ROP. However, the mechanism of early inflammation that triggers detrimental effects in the retina during ROP is still unclear and such inflammation is difficult to evaluate and predict .…”
Section: Discussionmentioning
confidence: 99%